THE IMPLEMENTATION OF CONTEXTUAL TEACHING LEARNING APPROACH IN TEACHING READING COMPREHENSION TO ANALYTICAL EXPOSITION TEXT - Dendy Aprilian; Mundriyah Y Pamungkas (PROJECT (Professional Journal of English Education), 2021)
English is a language that is found in all fields of Education, which makes English as a language skill that must be mastered by students.  There are four skills in learning English namely; reading, writing, speaking and listening. Reading comprehension is one of the skills which is important to develop by all learners because by reading people can improve their knowledge. The problems were the students had poor vocabulary. The researcher applies (CTL) Contextual Teaching Learning approach, to help students understand English-language reading. The objectives of this research entitled “the implementation of contextual teaching-learning approach in teaching reading comprehension to analytical exposition text” was to found out the implementation of the scenario and the students' responses in teaching-learning reading comprehension. This study used descriptive qualitative as a research design. The subject of this research was the grade XI of students’ senior high school in Cimahi consisted of 20 students. The results of this research showed CTL was successfully implemented based on scenarios prepared by the researchers. Using CTL was able to improve students' motivation in learning reading comprehension. It was expressed by students and teachers in the observation sheets and questionnaires.  Keywords:  Contextual Teaching Learning (CTL), Reading comprehension, Analytical exposition.